On Nested Sequents for Constructive Modal Logics - Lutz Strassburger; Anupam Das; Ryuta Arisaka (Logical Methods in Computer Science, 2015)
We present deductive systems for various modal logics that can be obtained from the constructive variant of the normal modal logic CK by adding combinations of the axioms d, t, b, 4, and 5. This includes the constructive variants of the standard modal logics K4, S4, and S5. We use for our presentation the formalism of nested sequents and give a syntactic proof of cut elimination.